Pemanfaatan Maggot Black Soldier Fly dalam Pengelolaan Sampah Organik: Tinjauan Literatur - Edo Nofriadi; Nindy Notrilauvia (Publikasi Indonesia, 2026)
Organic waste management has become one of the major environmental challenges in many developing countries, including Indonesia, due to the increasing volume of waste generated from population growth, urbanization, and changing consumption patterns. This study aims to analyze the potential utilization of Black Soldier Fly (BSF) larvae in organic waste management through a literature review approach. The research employed a qualitative method using literature study by collecting and analyzing various scientific references from journals, books, and related research reports published within the last ten years. The findings indicate that BSF larvae possess high efficiency in reducing organic waste volume through the bioconversion process while simultaneously producing valuable by-products such as protein-rich biomass for animal feed and organic fertilizer residues. In addition to environmental benefits through waste reduction and greenhouse gas mitigation, BSF technology also provides economic opportunities and social benefits by encouraging community-based waste management and circular economy practices. However, several challenges remain, including technical cultivation constraints, limited public awareness, inadequate regulatory support, and market development for derivative products. In conclusion, BSF bioconversion technology has strong potential as a sustainable organic waste management solution and requires further support through research, policy development, and community empowerment programs